African studies: Evolution, challenges, and prospects - Sackey, B.M. (Changing Perspectives on the Social Sciences in Ghana, 2014)
The establishment of African Studies at the Institute of African Studies in the University of Ghana, Legon, could be rationalised as a two-fold initiative: to portray the independence of African people in terms of a paradigm shift in academic curricula, and to be a channel in leading the processes of decolonising the minds of a people just liberated from foreign domination. However, Africa Studies is constantly challenged on its relevance and comparability with other disciplines in both western and African scholarship. This chapter examines the scope of this ideology in contemporary times, and the extent to which African Studies has lived up to the mandate for its establishment. This chapter examines African Studies from its short-lived evolution at the School of African Studies from 1949 to 1950 to its current niche in the Institute of African Studies, established in 1961 and inaugurated in 1963. It examines some of its challenges and prospects and discusses the lingering question on the relevance of African Studies in modern scholarship, drawing on published material available to me as well as my own interviews with past and present students of African Studies, faculty, and some members of the public. The chapter also compares the structure of African Studies at the University of Ghana, Legon and University of Cape Coast, Ghana, which are different, yet complementary. The study affirmed that regardless of its challenges and continued denigration, African Studies, enables students to know and understand their roots, inherited past traditions, norms and lore, and above all, to redefine and uphold African consciousness in all aspects of life. As any multi-disciplinary field, African Studies should be open for controversies and divergences as such ambivalences could be desirable for its sustenance.
Keywords: Academia; African Studies; Curricula; Ghana; Kwame Nkrumah